Strategi Pengembangan Budaya Organisasi dalam Meningkatkan Mutu Pendidikan - Bambang Wiyono (JIEM: Journal of Islamic Education and Manajemen, 2021)
The culture of the organization does not exist simply, but must be created. maintained, and strengthened, even altered to conform to the internal and external demands of the organization. Organizational culture will affect the effectiveness of the organization. So far many studies have concluded that a strong organizational culture will make members more satisfied, motivated and have a great commitment to the organization. In addition, a strong organizational culture will be able to increase the commitment, enthusiasm, and loyalty of members to the organization. Organizational culture will influence individuals and organizational processes, so culture will put pressure on people in the organization to think and act in a way that is consistent with existing culture. The organizational culture of educational institutions is strongly influenced by leadership behavior. Good leadership behavior will be able to create a conducive organizational culture